High-flexoelectric BaTiO3-based ceramic and preparation method thereof
By combining discharge plasma sintering and heat treatment, a BaTiO3-based ceramic with high flexural electrical properties was prepared, which solved the problems of long preparation time and high energy consumption of traditional sintering methods, and achieved rapid and low-energy-consuming high-performance ceramic preparation.
Patent Information
- Application Number
- CN202510024199.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-08
AI Technical Summary
The traditional sintering method takes a long time and high energy consumption to prepare BaTiO3-based ceramics with high flexibility, making it difficult to meet the needs of rapid preparation.
A BaTiO3-based ceramic with high flexural electrical properties was prepared by combining discharge plasma sintering (SPS) and heat treatment.
It achieves shortening the preparation time, reducing energy consumption, and at the same time improving the flexural electrical coefficient of the ceramic to reach 8 mC/m, which is far higher than the performance of the traditional muffle furnace sintering method.
Smart Images

Figure CN119775002A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, in particular to a high flexoelectric BaTiO 3 Base ceramics and preparation methods thereof. Background Art
[0002] The flexoelectric effect is a coupling effect that produces polarization response or strain under non-uniform strain or non-uniform electric field. It can exist in all materials and has potential applications in sensors, actuators, transducers, etc. It can also regulate many physical properties by converting strain gradient fields into electric fields, thus gaining great attention and research. 3 The base ceramic has a very prominent flexoelectric response.
[0003] At present, the preparation of ceramics with high flexoelectric properties requires the addition of polymer binders for granulation (about 1 hour), drying (about 3 hours), tablet pressing (about 1 hour), muffle grate molding (about 14 hours) and muffle furnace sintering (about 17 hours). It takes about 36 hours in total and consumes a lot of energy. This method is called conventional sintering (CS).
[0004] The traditional sintering method requires a long preparation time, so it is necessary to provide a new high flexoelectric BaTiO 3 Ceramic-based method. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a high flexoelectric BaTiO 3 BaTiO 3 The base ceramic has an oxygen vacancy gradient that gradually increases from the ceramic surface to the interior of the ceramic, and a surface inhomogeneous strain layer from the surface to the interior, and its flexoelectric coefficient is as high as 8 mC / m.
[0006] The present invention also provides the above-mentioned high flexoelectric BaTiO 3 The invention discloses a method for preparing a base ceramic. The method is time-saving, reduces preparation time and reduces energy consumption.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme:
[0008] A high flexoelectric BaTiO 3 Based ceramics, the high flexoelectric BaTiO 3 The base ceramic has an oxygen vacancy gradient, wherein the oxygen vacancy gradient is that the oxygen vacancies gradually increase from the surface layer to the interior of the ceramic, and the BaTiO 3 Base ceramics include BaTiO 3Ceramics and BaTiO doped with other elements 3 Base ceramic.
[0009] Wherein, the thickness of the ceramic surface layer is 1-4 μm.
[0010] Wherein, the high flexoelectric BaTiO 3 The base ceramic has an inhomogeneous strain layer, and the strain of the inhomogeneous strain layer gradually decreases from the surface to the inside.
[0011] The high flexoelectric BaTiO 3 The preparation method of the base ceramic comprises the following steps:
[0012] (1) Mold making: BaTiO 3 The base powder is loaded into the mold and pre-pressed;
[0013] (2) Spark plasma sintering: The mold is placed in a spark plasma sintering furnace, a certain axial pressure is applied to the mold, and the spark plasma sintering furnace is controlled to quickly heat up to the conventional sintering temperature, and then cooled after keeping the temperature for 4 to 7 minutes to obtain BaTiO 3 Based sintered ceramics;
[0014] (3) Annealing treatment: 3 The high flexural electrical BaTiO 3 The annealing temperature of the annealing treatment is 650~750 ℃, the holding time is 0.5~1.5 hours, and the cooling rate is 4~8 ℃ / min.
[0015] Wherein, before the annealing treatment, the BaTiO 3 Steps for grinding sintered ceramics.
[0016] Wherein, the heating rate in step (2) is 60-70 °C / min.
[0017] Wherein, the plasma sintering in step (2) is carried out under vacuum conditions.
[0018] The traditional sintering temperature refers to the sintering temperature of a muffle furnace.
[0019] The stress applied to the mold in step (2) is in the range of 45-58 MPa.
[0020] The beneficial effects of the present invention are as follows:
[0021] (1) High flexoelectric BaTiO 3BaTiO2 with oxygen vacancy gradient and surface inhomogeneous strain layer from the surface to the inside is obtained by regulating the oxygen vacancy gradient and strain of the ceramic surface layer. 3 BaTiO 3 Base ceramic.
[0022] (2) The present invention proposes a method for rapidly preparing high flexoelectric BaTiO by combining spark plasma sintering (SPS) with heat treatment. 3 BaTiO-based ceramics. During the preparation process, SPS can be used to quickly sinter BaTiO 3 BaTiO2 is a kind of ceramics, which is then sintered by spark plasma. 3 The base ceramic forms a polar surface layer to compensate for the shortcomings of this sintering method, such as small grain size and strong conductivity, which deteriorate the flexoelectricity. The oxygen vacancy gradient and strain of the surface layer and near the surface layer are regulated to form an oxygen vacancy gradient and a surface uneven strain layer from the surface to the inside. The entire preparation takes about 6 hours at most, which reduces the preparation time and energy consumption compared to the muffle furnace sintering (CS) method, and a flexoelectric BaTiO with a flexoelectric coefficient of up to ~8 mC / m can be obtained. 3 Ceramics, much higher than BaTiO sintered in traditional muffle furnace 3 Flexoelectric properties (≤1 mC / m). BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 BaTiO prepared for X-ray photoelectron spectroscopy test example 3 O1s electronic chemical states on different surfaces of ceramics.
[0024] Figure 2 The BaTiO prepared in Example 1 and Comparative Example 1 are 3 Flexoelectric coefficient of ceramics.
[0025] Figure 3 The BaTiO prepared in Example 1, Comparative Example 2 and Comparative Example 3 are 3 Flexoelectric coefficient of ceramics. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0027] The present invention provides a high flexoelectric BaTiO3 Based ceramics, the high flexoelectric BaTiO 3 The base ceramic has an oxygen vacancy gradient, where oxygen vacancies gradually increase from the ceramic surface to the interior of the ceramic. 3 The oxygen vacancies of the base ceramics show a gradually increasing trend from the surface to the center.
[0028] Furthermore, the high flexoelectric BaTiO 3 The base ceramic also has an inhomogeneous strain layer, in which the strain gradually decreases from the surface to the inside. The strain has a tendency to gradually decrease from the surface.
[0029] The inventors found that oxygen vacancies and surface strain gradient layers are the main factors affecting the thermal conductivity of BaTiO 3 The flexoelectric coefficient of the base ceramic can be changed by regulating the oxygen vacancies and strain on the surface and inside of the ceramic, thereby obtaining a high flexoelectric ceramic.
[0030] Preferably, the thickness of the surface layer is 1-4 μm.
[0031] Wherein, the BaTiO 3 Base ceramics include BaTiO 3 Ceramics and BaTiO doped with other elements 3 BaTiO doped with other elements 3 The base ceramic can be barium calcium zirconate titanate (BCZT), barium strontium titanate (BST), etc. 3 Base ceramic.
[0032] The high flexoelectric BaTiO 3 The preparation method of the base ceramic comprises the following steps:
[0033] (1) Mold making: BaTiO 3 The base powder is loaded into the mold and pre-pressed;
[0034] (2) Spark plasma sintering: The mold is placed in a spark plasma sintering furnace, a certain axial pressure is applied to the mold, and the spark plasma sintering furnace is controlled to quickly heat up to the conventional sintering temperature, and then cooled after keeping the temperature for 4 to 7 minutes to obtain BaTiO 3 Based sintered ceramics;
[0035] (3) Annealing treatment: 3 The high flexural electrical BaTiO 3 Preferably, the annealing process can be carried out in a muffle furnace, which does not require a faster heating rate.
[0036] The preparation method of the present invention adopts spark plasma sintering to generate a large number of oxygen vacancies by rapidly heating up; then, a low temperature and short-time annealing treatment is performed to fill the oxygen vacancies in part of the surface layer and the vicinity of the surface layer, so that an oxygen vacancy gradient is formed. 3 The base ceramic still has a large number of oxygen vacancies, which improves its flexoelectric coefficient.
[0037] Preferably, before the annealing treatment, the BaTiO 3 The step of grinding sintered ceramics. Grinding is to create mechanical stress on the surface of the ceramic sheet, forming a surface strain gradient layer during the subsequent annealing process, which helps to enhance the flexoelectric effect.
[0038] More preferably, the heating rate in step (2) is 60-70 °C / min. Rapid heating can form more oxygen vacancies.
[0039] Preferably, the annealing temperature of the annealing treatment is 650-750°C, the holding time is 0.5-1.5 hours, and the cooling rate is about 4-8°C / min. In order to form an oxygen vacancy gradient, the present invention adopts a low temperature and short time annealing treatment, the purpose of which is to allow oxygen to fill part of the oxygen vacancies in the ceramic surface layer and its vicinity.
[0040] Preferably, there is no requirement for the temperature rise of the annealing treatment in step (3), and the sooner the annealing temperature is reached, the better.
[0041] Preferably, the plasma sintering in step (2) is performed under vacuum conditions. Vacuum conditions help to form more oxygen vacancies. However, the annealing treatment needs to be performed under oxygen conditions, and the oxygen concentration is preferably greater than 1% (volume ratio).
[0042] The conventional sintering temperature refers to the sintering temperature of a muffle furnace. 3 The muffle furnace sintering temperature of ceramics is 1300±50°C, the sintering temperature of BCZT ceramics is 1500±50°C, and the sintering temperature of BST ceramics is 1350~1500°C. Therefore, the traditional sintering temperature in this step is 1200~1600°C, and the specific temperature can be determined according to the ceramics to be prepared.
[0043] The stress applied to the mold in step (2) is in the range of 45-58 MPa.
[0044] Example 1
[0045] 4 g of BaTiO prepared by solid phase method was added 3The powder was placed in a graphite mold (inner diameter 12.5 mm) and compacted. After the mold containing the powder was placed in the designated position in the SPS furnace chamber, it was evacuated (<5 Pa). The vacuum was maintained, and a pressure of 5.1 KN (45.1 MPa) was applied to the powder by uniformly compressing the graphite indenter. At the same time, a large current was applied to the mold to increase the temperature. Finally, the temperature was rapidly increased to 1300 °C at 65 °C / min (much higher than the muffle furnace heating rate of 4~5 °C / min). After keeping the temperature for 5 minutes, the temperature was lowered to obtain a BaTiO with a thickness of about 5 mm. 3 For ceramics, this process takes about 1 hour. Annealing is carried out in air atmosphere.
[0046] The ceramics obtained by SPS were polished into a series of discs with a thickness of 0.6~1.5 mm using diamond cutting machine sandpaper, and then heated to 700℃ in a muffle furnace at a heating rate of 8℃ / min. After keeping warm for 1 hour, the temperature was cooled at a cooling rate of 4℃ / min; it took about 5.5 hours.
[0047] The bulk ceramic disc obtained by plasma sintering in this embodiment is about 5 mm thick. In order to facilitate the generation of strain gradient, we need to cut the sample into thinner ceramic discs, for example, 6 discs. The cut discs are polished and then annealed at the above 650~750 ℃ to obtain high flexural electrical ceramics.
[0048] Gold electrodes were sputtered on both sides of the prepared ceramic, and then the effective flexoelectric coefficient was tested using the dot-ring method. At 110Hz, BaTiO 3 The effective flexoelectric coefficient of ceramics can reach about 8 mC / m.
[0049] Figure 1 The X-ray photoelectron spectroscopy test of BaTiO in Example 1 3 The O1s electronic chemical state on the ceramic surface. Figure 1 (a) is the unannealed spark plasma sintered BaTiO 3 O1s on ceramic surface, Figure 1 (b) is BaTiO after annealing in air 3 O1s on ceramic surface, Figure 1 (c) is the BaTiO after annealing. 3 O1s at 3 μm on the ceramic surface. In addition to the lattice oxygen peak, the other peaks in the figure are related to oxygen vacancies. The peak area is proportional to the oxygen vacancy concentration, and the intensity ratio is as shown in the following table.
[0050] Table 1 Area ratio of oxygen vacancy peak to lattice oxygen peak
[0051]
[0052] contrast Figure 1 (a) and (b) show that the BaTiO2 obtained in Example 1 after annealing in air is 3 The peak intensity ratio of the ceramics related to oxygen vacancies decreases, indicating that the annealed BaTiO 3 The oxygen vacancy concentration in the ceramic surface layer decreases, so annealing in air helps to regulate the oxygen vacancy concentration. 3 The oxygen vacancy gradient is formed on the ceramic surface layer. We compare the peak intensity ratio of the samples before and after removing the surface layer (about 3 μm) ( Figure 1 In (b) and (c) of Figure 2, it can be found that the peak intensity ratio of the ceramic with the surface layer removed increases and is closer to the oxygen vacancy peak intensity before annealing. Therefore, after removing 3 μm of BaTiO 3 The ceramic surface is almost equivalent to the original BaTiO 3 Therefore, it can be explained that after annealing, BaTiO 3 The oxygen vacancy concentration on the ceramic surface is lower than that in the bulk phase, forming an oxygen vacancy gradient. At the same time, after removing the surface layer of 3 μm (i.e., removing the oxygen vacancy gradient), the BaTiO 3 The flexoelectric coefficient of the ceramic drops sharply from the original ~8000 μC / m to ~320 μC / m, which is also much larger than the flexoelectric coefficient of the sample before annealing, indicating that the oxygen vacancy gradient has an important contribution to the flexoelectric coefficient.
[0053] Comparative Example 1
[0054] The remaining steps are the same as those in Example 1, except that the annealing is performed in an argon atmosphere.
[0055] Figure 2 The BaTiO prepared in Example 1 and Comparative Example 1 3 Comparison of flexoelectric coefficients of ceramics. Figure 2 It can be seen that the BaTiO annealed in air 3 The flexoelectric coefficient of the ceramic is much higher than that of BaTiO obtained in argon. 3 Ceramics. Therefore, annealing must be carried out in the presence of oxygen.
[0056] Comparative Example 2
[0057] The remaining steps of this embodiment are the same as those of embodiment 1, except that the cooling condition for annealing is to cool the furnace to 300° C. and then rapidly cool the furnace (the cooling rate is 500-600° C. / min, referred to as rapid cooling).
[0058] Comparative Example 3
[0059] This example is to prepare the BaTiO 3 The ceramic was heated to 300 °C again and then slowly cooled (cooling rate was 5 °C / min).
[0060] Figure 3 The BaTiO obtained in Example 1, Comparative Example 2 and Comparative Example 3 3 Flexoelectric coefficient of ceramics. Figure 3 It can be seen that the annealing cooling rate has an important effect on the BaTiO 3 The flexoelectric coefficient of ceramics has an important influence. Figure 3 , we annealed the sample to 300 °C and then quickly cooled it to room temperature (Comparative Example 2), and the flexoelectric coefficient was only ~5400 μC / m, which is much smaller than the slowly cooled sample (Example 1). If the rapidly cooled sample is raised to 300 °C again and then slowly cooled (Comparative Example 3), the flexoelectric coefficient can be restored to the flexoelectric coefficient of the original slowly cooled sample. This shows that the annealing and slow cooling adopted by the present invention are helpful to release the stress of the surface layer, produce a thicker strain gradient, and are beneficial to the flexoelectric properties. However, the stress cannot be released in time during rapid cooling, which is not conducive to the formation of the strain gradient surface layer and the flexoelectric properties.
[0061] Example 2
[0062] 4 g of BaTiO prepared by solid phase method was added 3 The powder was placed in a graphite mold (12.5 mm inner diameter) and compacted. The mold containing the powder was placed in the designated position in the SPS furnace chamber and vacuumed (<5 pa). The vacuum was maintained and an axial pressure of 50 MPa was applied to the powder by uniformly compressing the graphite indenter. At the same time, a large current was applied to the mold to increase the temperature. Finally, the temperature was rapidly increased to 1300 °C at 60 °C / min. After keeping the temperature for 7 min, the temperature was lowered to obtain a BaTiO layer with a thickness of about 5 mm. 3 For ceramics, this process takes about 1 hour. Annealing is carried out in air atmosphere.
[0063] The ceramics obtained by SPS were polished into a series of discs with a thickness of 0.6~1.5 mm using diamond cutting machine sandpaper, and then heated to 750℃ in a muffle furnace at a heating rate of 10℃ / min, kept at this temperature for 0.5 hours and then cooled at a cooling rate of 6℃ / min; it took about 5.5 hours.
[0064] Gold electrodes were sputtered on both sides of the prepared ceramic, and the flexoelectric coefficient was tested using the dot-ring method. At 110Hz, BaTiO 3 The flexoelectric coefficient of ceramics is about 8 mC / m.
[0065] Example 3
[0066] 4 g of BST (Ba 0.67 Sr 0.33 TiO 3 ) The powder is placed in a graphite mold (inner diameter 12.5 mm) and compacted. The mold containing the powder is placed in the specified position in the SPS furnace chamber and evacuated (<5 Pa). The vacuum is maintained, and a pressure of 58 MPa is applied to the powder by uniformly compressing the graphite indenter. At the same time, a large current is applied to the mold to increase the temperature. Finally, the temperature is rapidly increased to 1400 °C at 70 °C / min, and the temperature is cooled after 4 minutes of heat preservation to obtain BST ceramics. This process takes about 1 hour.
[0067] The ceramics obtained by SPS were polished into a series of discs with a thickness of 0.6-1.5 mm by diamond cutting machine sandpaper, and then heated to 650°C at a rate of 6°C / min in a muffle furnace, kept at this temperature for 1.5 hours, and then cooled at a rate of 8°C / min; it took about 5.5 hours. Annealing was carried out in air atmosphere.
[0068] Gold electrodes were sputtered on both sides of the prepared ceramic, and the flexoelectric coefficient was tested using the dot-ring method. It is found that at 110 Hz, the flexoelectric coefficient of BST ceramics is about 6 mC / m.
[0069] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0070] The parts not elaborated in detail in the description of the present invention belong to the known technology in the art. The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included in the scope of the present invention.
Claims
1. A high flexoelectric BaTiO3-based ceramic, characterized in that: The high flexoelectric BaTiO3-based ceramic has an oxygen vacancy gradient, wherein the oxygen vacancy gradient gradually increases from the surface layer to the interior of the ceramic. The BaTiO3-based ceramic includes BaTiO3 ceramic and BaTiO3-based ceramic doped with other elements.
2. The high flexoelectric BaTiO3-based ceramic according to claim 1, characterized in that: The thickness of the ceramic surface layer is 1-4 μm.
3. The high flexoelectric BaTiO3-based ceramic according to claim 1, characterized in that: The high flexural electrical BaTiO3-based ceramic has an inhomogeneous strain layer, and the strain of the inhomogeneous strain layer gradually decreases from the surface to the inside.
4. The method for preparing the high flexoelectric BaTiO3-based ceramic according to any one of claims 1 to 3, characterized in that: The steps include: (1) Mold filling: Place the BaTiO3-based powder into the mold and pre-press it; (2) Spark plasma sintering: placing the mold in a spark plasma sintering furnace, applying axial pressure to the mold, controlling the spark plasma sintering furnace to quickly heat up to a conventional sintering temperature, keeping the temperature for 4 to 7 minutes, and then cooling down to obtain a BaTiO3-based sintered ceramic; (3) Annealing treatment: The high flexoelectric BaTiO3-based ceramic can be obtained by annealing the BaTiO3-based sintered ceramic.
5. The preparation method according to claim 4, characterized in that: The method also includes a step of grinding the BaTiO3 sintered ceramic before the annealing treatment.
6. The preparation method according to claim 4, characterized in that: The heating rate in step (2) is 60-70 °C / min.
7. The preparation method according to claim 4, characterized in that: The annealing temperature of the annealing treatment in step (3) is 650-750°C, the holding time is 0.5-1.5 hours, and the cooling rate is 4-8°C / min.
8. The preparation method according to claim 4, characterized in that: The plasma sintering in step (2) is carried out under vacuum conditions.
9. The preparation method according to claim 4, characterized in that: The conventional sintering temperature refers to the sintering temperature of a muffle furnace.
10. The preparation method according to claim 4, characterized in that: The stress applied to the mold in step (2) ranges from 45 to 58 MPa.